2018
DOI: 10.1080/19476337.2018.1430707
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of hesperidin from lime peel (Citrus limettaRisso) in solid fermentation byAspergillus saitoi

Abstract: The aim of this study was to assess the ability of the biotransformation of hesperidin from lime peel by Aspergillus saitoi in solid fermentation. The decrease of hesperidin by High-Performance Liquid Chromatography (HPLC) was monitored during 8 days of fermentation. The radical scavenging activity of DPPH · and ABTS ·+ increased to 5.8 and 11 times, respectively, after 6 days of fermentation compared with unfermented lime peel. Similarly, the phenolic content of the extract of fermented lime peel was 8.66 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The previous research was on the biotransformation of the lime peel by Aspergillus saitoi in solid medium. The ABTS •+ and DPPH • radical scavenging activity of the biotransformation extract was increased compared with unfermented lime peel [18].…”
Section: In Vitro Anti-inflammatory Activitymentioning
confidence: 89%
“…The previous research was on the biotransformation of the lime peel by Aspergillus saitoi in solid medium. The ABTS •+ and DPPH • radical scavenging activity of the biotransformation extract was increased compared with unfermented lime peel [18].…”
Section: In Vitro Anti-inflammatory Activitymentioning
confidence: 89%
“…Hesperidin in lime peel had a 5.8 to 11 times increase in antioxidant activity compared to unfermented lime peel. The high antioxidant activity of fermented lime peel may be related to the biotransformation of hesperidin to hydroxy flavanone and aglycone, given that other low-molecular-weight phenolic compounds are produced [66].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Compound 37 showed molecular ions at [M-H] − m/z 301.0717, labelled as hesperetin with MS 2 ions at m/z 283 and m/z 177, and was detected in the colonic fermentation of MPP extracts. Past studies reported that the microbial metabolism of hesperidin and naringenin in lemon peel increased the release of hesperetin during solid-state fermentation [16].…”
Section: Flavonoidsmentioning
confidence: 99%